Correlation Between Protein Intake and Nitrogen Balance of Surgical Patients in Anesthesiology and Intensive Care Installation, Sanglah General Hospital, Denpasar, Bali, Indonesia - Wiryana, Made; Sinardja, I Ketut; Senapathi, Tjokorda Gde Agung; Widnyana, I Made Gede; Panji, Putu Agus Surya; Aryabiantara, I Wayan; Cindryani, Marilaeta (BALI MEDICAL JOURNAL, 2016)
Background: A cell injury from surgical stress in a trauma or a non-trauma case will induce a hyper metabolic response in which the protein degradation increases, the somatic protein synthesis decreases and the amino acid catabolism increases. Thus, the pyper metabolic response contributes to nitrogen loss in urine. This response, without an adequate nutrition, will lead an iatrogenic malnutrition and deterioration. A balance nitrogen formula through urinary urea nitrogen is one of many nutrition evaluation methods. This method aids in evaluating the daily nutrition status and it can be the baseline data for daily intake. Objective: To find a correlation between the protein intake and the nitrogen balance of the surgical patients in anesthesiology and intensive care installation, Sanglah General Hospital, Denpasar, Bali. Methods: Fifty-one surgical patients with trauma and non-trauma cases were observed for their protein intake for 2-3 days continuously. Moreover, they were evaluated for their nitrogen balance based on the urinary urea nitrogen per 24 hours for 2-3 days. For statistical analysis, we utilized Shapiro-Francia, Shapiro-Wilk, Spearman Frank correlation, two-sample t test, and multivariate regression analysis in Strata SE 12.1. Results: The correlation between the protein intake and the nitrogen balance on the first day was ra=0.50 (p<0.05), on the second day ra=0.70 (p<0,05), and on the third day ra=0.740 (p<0,05) Conclusions: There is a correlation between the protein intake and the nitrogen balance of surgical patients in Anesthesiology and Intensive Care Installation Sanglah General Hospital Denpasar.